2016
DOI: 10.1139/cjss-2015-0071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymer-coated urea on nitrous oxide emission in zero-till and conventionally tilled silage corn

Abstract: Little is known about nitrous oxide (N 2 O) emission from silage corn (Zea mays L.). Studies have shown that controlled-release N fertilizers have the potential to reduce N 2 O emissions, compared with conventional N fertilizers. This 2-year field study compared N 2 O emissions from urea fertilizer and a slow-release polymer-coated urea (CRU) applied to silage corn on soils managed with conventional tillage (CT) and zero tillage (ZT). The study was conducted on a silty loam soil in the cool, moist climate of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…The current study found that there was no significant difference in soil organic matter caused by tillage system (P = 0.1072). It is possible that this represents a type II error because previous work at the study site found that soil organic C (by dry combustion) was significantly greater (13%) with no-till than conventional tillage (Hunt et al 2016). In this study, soil organic matter was 9% greater with no-till than conventional tillage.…”
Section: Resultscontrasting
confidence: 49%
“…The current study found that there was no significant difference in soil organic matter caused by tillage system (P = 0.1072). It is possible that this represents a type II error because previous work at the study site found that soil organic C (by dry combustion) was significantly greater (13%) with no-till than conventional tillage (Hunt et al 2016). In this study, soil organic matter was 9% greater with no-till than conventional tillage.…”
Section: Resultscontrasting
confidence: 49%
“…Rochette et al (2018) did not investigate the effects of EEF, perhaps because there was only one Canadian study (Soon et al 2011) available at the time. Since 2017 however, there have been seven additional studies examining the effect of EEF on annual N 2 O emissions from Canadian agriculture with three studies unable to detect differences between EEF and regular synthetic N fertilizers (An et al 2021;An et al 2020;Yao et al 2020), two studies that noted reduced soil N 2 O emissions with EEF (Ferrari Machado et al 2020;Thilakarathna et al 2020), and two studies that found mixed results with EEF resulting in lower, similar and even greater emissions depending on other management practices and / or climate (Hunt et al 2016;Wood 2018). This range of results could be due to the use of different products or regional differences, perhaps related to soil moisture (Akiyama et al 2010) and temperature.…”
Section: Annual Emissionsmentioning
confidence: 99%
“…This result is similar to that for corn and slightly lower than that for soybeans when compared to a study summarizing 16 years of year-round emissions at the Elora site, the location used to estimate the correction factor of 1.4 in the study by Rochette et al (2008b), where the PWE was 38% and 43% of annual emissions for corn and soybean, respectively (Baral et al 2022). Also, while the statistical model and data set used here did not implicitly allow for a comparison of ecozones, the PWE for studies in the Pacific Maritime region was only 23% ± 1.6% of annual emissions (Hunt et al 2016(Hunt et al , 2019, which was noticeably lower than the other ecozones. Much of the data from the Pacific Maritime ecozone was for studies measuring emissions from manure applied to grass swards.…”
Section: Proportion Of Emissions During Non-growing Seasonmentioning
confidence: 99%
“…Bavin et al (2009) concluded that N fertilization was the primary factor regulating N 2 O fluxes in tillage and no-till treatments. It is clear that the tillage effect on N 2 O emissions depends on the location, climate, and management practices, so it is important to investigate not only SOC sequestration but also N 2 O emissions under well-drained soils since the benefits of no-till on SOC concentration need to be balanced against the effects on emissions (Fabrizzi et al, 2009;Hunt et al, 2016;Nicoloso et al, 2018).…”
Section: Introductionmentioning
confidence: 99%